IMMUNOMODULATORY FUNCTION OF DIBAZOL DRUG - Axmedov Shamshod Jamshidovich; Ergashov Bekhruzjon Komilovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Dibazol (2-benzylbenzimidazol hydrochloride or bendazol) is a drug possessing vasodilatation, antispasmodic and hypertensive properties [13], [14]. It has been commonly used in the treatment of hypertension, angina pectoris and cerebral vasospasm. However, it may not be used for elderly patients as a means of anti-hypertensive for a long time because of the anti-hypertensive effect of the decrease in cardiac ejection and possible deterioration of the electrocardiogram. Hence, investigating the binding of dibazol to BSA is very helpful for pharmacokinetics and the design of dosage.